DIFFERENTIATED ASSESSMENT INSTRUMENT: A DEVELOPMENT STUDY (A CASE STUDY OF GRADE XI STUDENTS IN THE FIRST SEMESTER OF SENIOR HIGH SCHOOL) - Maharani, Putu Rima; Nitiasih , Putu Kerti; Mahayanti, Ni Wayan Surya (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research focuses on the development of differentiated assessment instruments for 11th-grade students in the first semester of senior high school, aligned with the Emancipation Curriculum. The problem addressed in the study is the challenge teachers face in designing assessments that accommodate diverse learning styles—visual, auditory, read/write, and kinesthetic—while aligning with curriculum standards. The purpose of the study is to develop practical, tailored assessment tools that meet the varied needs of students and enhance the effectiveness of instruction. Utilizing the Design and Development (DnD) model by Richey and Klein (2007), the research involved a needs analysis through interviews, questionnaires, and document analysis at selected high schools in Buleleng, Bali. The study adopted a mixed-methods approach, with quantitative data analyzed using descriptive statistics, while qualitative data was examined through thematic analysis based on interviews and classroom observations. The results showed that teachers found it challenging to implement differentiated assessments due to the diverse learning preferences of students and the lack of resources. However, the developed assessment instruments were evaluated as "Good" by expert validators, with suggestions for further refinement to achieve excellence. These tools provide a practical framework for teachers to implement differentiated assessments that support personalized learning and align with the Emancipation Curriculum.